Need for Gastrostomy Tube in Periviable Infants - ElSeed Peterson, Erica E.; Roeckner, Jared T.; Deall, Taylor W.; Karn, Michele; Duncan, Jose R.; Flores-Torres, Jaime; Kumar, Ambuj; Randis, Tara M. (American Journal of Perinatology, 2024)
Objective We sought to identify clinical and demographic factors associated with gastrostomy tube (g-tube) placement in periviable infants.Study Design We conducted a single-center retrospective cohort study of live-born infants between 22 and 25 weeks' gestation. Infants not actively resuscitated and those with congenital anomalies were excluded from analysis.Results Of the 243 infants included, 158 survived until discharge. Of those that survived to discharge, 35 required g-tube prior to discharge. Maternal race/ethnicity (p = 0.006), intraventricular hemorrhage (p = 0.013), periventricular leukomalacia (p = 0.003), bronchopulmonary dysplasia (BPD; p ≤ 0.001), and singleton gestation (p = 0.009) were associated with need for gastrostomy. In a multivariable logistic regression, maternal Black race (Odds Ratio [OR] = 2.88; 95% confidence interval [CI]: 1.11–7.47; p = 0.029), singleton gestation (OR = 3.99; 95% CI: 1.28–12.4; p = 0.017) and BPD (zero g-tube placement in the no BPD arm; p ≤ 0.001) were associated with need for g-tube.Conclusion A high percentage of periviable infants surviving until discharge require g-tube at our institution. In this single-center retrospective study, we noted that maternal Black race, singleton gestation, and BPD were associated with increased risk for g-tube placement in infants born between 22 and 25 weeks' gestation. The finding of increased risk with maternal Black race is consistent with previous reports of racial/ethnic disparities in preterm morbidities. Additional studies examining factors associated with successful achievement of oral feedings in preterm infants are necessary and will inform future efforts to advance equity in newborn health.Key Points
Keywords: periviable infant; gastrostomy tube; extremely low birth weight infant; periviable outcomes; medical device